Plant-mediated synthesis of nanoparticles and their applications: A review. (July 2023) - Rani, Neeru; Singh, Permender; Kumar, Sandeep; Kumar, Parmod; Bhankar, Vinita; Kumar, Krishan
Highlights: Nanotechnology has received much attention recently due to its significant applications in various fields. The physiochemical routes for the fabrication of nanoparticles are quite expensive and hazardous. Green synthesis employs non-toxic, natural, easily and widely available precursors. We summarized various applications of green synthesised nanoparticles including biomedical applications. Abstract: In the present era, nanoparticles have attracted the scientific community all across the globe. It is because of their outstanding physical, chemical and biological properties such as optical, magnetic, photocatalytic and sensing. Over the years, different physical and chemicals methods have been used for nanomaterials synthesis. Unfortunately, these routes are quite expensive, involve the use of toxic chemicals, possibility of production of hazardous secondary by-product, and ultimately lead to an environmental footmark. Therefore, it is the need of the hour to innovate a simple, cost-effective and eco-friendly alternative. Now a days, synthesis of nanomaterials using plant extracts as precursor is gaining huge attention due to its facile, eco-friendly and non-toxic nature. Several molecular entities including flavonoids, terpenoids, alcohols, carbohydrates, sugars, polyphenols present in plant extracts act as stabilizing and reducing agents for the synthesis. Green synthesis has proved to be a potential alternative to traditional routes for nanomaterials synthesis. Graphical abstract: Image, graphical abstract